The genomic case against genetic determinism - Robinson, Gene E.; Bliss, Rina; Hudson, Matthew E. (PLoS biology, 2024)
Animal studies reveal that the molecular wiring of the brain can be altered by heredity, the environment, and their interaction. A deeper molecular understanding of these interactions could be a potent antidote to societal concerns of genetic determinism for human behavior, but this requires a paradigm that extends beyond traditional genome-wide association study (GWAS).